Characterization of two closely related α-amylase paralogs in the bark beetle, Ips typographus (L.) - Viktorinova, Ivana; Kucerova, Lucie; Bohmova, Marta; Henry, Ian; Jindra, Marek; Dolezal, Petr; Zurovcova, Martina; Zurovec, Michal (Archives of insect biochemistry and physiology, 2011)
Ips typographus (L.), the eight-spined spruce bark beetle, causes severe damage throughout Eurasian spruce forests and suitable nuclear markers are needed in order to study its population structure on a genetic level. Two closely related genes encoding α-amylase in I. typographus were characterized and named AmyA and AmyB. Both α-amylase paralogs consisted of six exons and five introns. AmyA encodes a polypeptide of 483 amino acids, whereas AmyB has two alternative transcripts encoding polypeptides of 483 and 370 amino acids. The expression levels of both genes were high during larval stage and adulthood. The AmyB transcripts were absent in the pupal stage. A modification of the allozyme staining method allowed us to detect two clusters of bands on the electrophoretic gel that may correspond to the two α-amylase genes. There was a correlation between the lack of AmyB expression in pupa and the absence of the fast migrating isozyme cluster at this stage, suggesting that the faster migrating isoforms are products of the AmyB gene, whereas the slowly migrating bands are derived from the AmyA.
Keywords: Base Sequence; Electrophoresis, Polyacrylamide Gel; Isoenzymes; Sequence Homology, Amino Acid; ektroforéza na škrobovém gelu; sekvenční homologie aminokyselin; fylogeneze; alpha-Amylases; Electrophoresis, Starch Gel; Cloning, Molecular; sekvence nukleotidů; Molecular Sequence Data; Coleoptera; elektroforéza v polyakrylamidovém gelu; RNA, Messenger; Insect Proteins; sekvence aminokyselin; messenger RNA; Animals; alfa-amylasy; zvířata; izoenzymy; Phylogeny; molekulární sekvence - údaje; klonování DNA; brouci; Amino Acid Sequence; hmyzí proteiny